The "Lenin’s fall" as an example of de/occupation of consciousness - Bohutskyi, Artem (Ukrainian Cultural Studies, 2025)
Background. The analysis of transformations in the symbolic space of Ukraine after the Revolution of Dignity is based on theoretical postcolonialism and memory studies. The author analyses the physical and semantic dismantling of Soviet monuments as one of the practices associated with the rethinking of collective memory. The relationship between the physical de/construction of Soviet monuments and the transformations associated with changes in public consciousness in the context of de/colonisation is traced. The relevance of this study is grounded in several factors. First, the dismantling (semantic and physical) of Lenin monuments and monuments that are markers of the Russian Empire in general is an important step in the process of decolonisation of Ukraine and is a form of protection of national identity. Second, this phenomenon has intensified academic discussions on the role of the Soviet-imperial heritage in contemporary Ukrainian commemorative discourse. Third, “Lenin's fall” has been a pivotal factor influencing subsequent cultural and geopolitical transformations in Ukraine and beyond. The purpose of the study is to analyze the phenomenon of "Lenin's fall" as an integral part of the process of decommunization and decolonization of the Ukrainian sociocultural space.Methods. To achieve this goal, a comprehensive interdisciplinary approach is employed. Pierre Nora's concept of ‘sites of memory' provides a framework for analyzing Soviet monuments as constructed symbols of collective memory and for exploring their role in shaping national identity. The theory of cultural memory developed by Aleida and Jan Assmann provides a wide range of tools for analyzing the transformational processes associated with collective perceptions of the past. The theory of ‘symbolic capital' proposed by Pierre Bourdieu helps to analyze the transformational processes between social agents related to the changes in the monumental landscape. The research is  primarily based on the cultural studies approach to assess changes in the semantic space and on historical and comparative method to analyze the phenomenon of ‘Lenin's fall' in the context of decolonization processes.Results. It has been established that the phenomenon of Lenin's fall has undergone a number of transformations: the spontaneous destruction of the Lenin monument on Shevchenko Boulevard on 8 December 2013 has turned into a systematic and now legally supported process of decolonization. The article traces the transformations of the Ukrainian sociocultural environment resulting from the processes of decolonization/de-imperialisation/de-Sovietisation. The author emphasizes the need to continue the policy of meaningful cleansing and protection of the Ukrainian cultural environment from the influence of Moscow and its proxies.Conclusions. The study of the phenomenon of "Lenin's fall" confirms the need for a comprehensive approach to the study of processes related to the decolonization of symbolic space. The physical deconstruction or, conversely, the installation of Soviet monuments is necessarily accompanied by transformational changes in cultural narratives. The results of the study can be used for further research on decolonization processes and the improvement of national memory policy as an important part of protecting national identity from Russian imperial resentment.
Keywords: cultural dimension; interdisciplinary; cultural issues; cultural practices; Lenin's fall; Russian-Ukrainian war; sociocultural transformations; Ukrainian identity